Effect of Temperature and pH on Early Hydration Rate and Apparent Activation Energy of Alkali-Activated Slag - Ping Li; Jianhui Tang; Xudong Chen; Yin Bai; Qiyao Li (Advances in Materials Science and Engineering)
In order to investigate the effect of temperature and pH on the early hydration rate of alkali-activated slag (AAS), NaOH was used as alkali activator, and the nonevaporable water (NEW) content of the slag paste at different temperatures (5, 20 and 35°C) and pH (12.10, 12.55, 13.02, and 13.58) was measured. On the basis of the Arrhenius formula, the hydration rate of slag was characterized by the content of nonevaporative water, and the apparent activation energy of slag hydration at different pH was also obtained. The early hydration rate of slag was significantly affected by temperature and pH of activator solution. The apparent activation energy Ea of slag decreased with the increase of pH, and there was a good linear relationship between them. When pH was less than 13.02, increasing the temperature can accelerate the hydration rate of slag. However, under the condition of high pH (pH = 13.58), the hydration rate of slag was negatively correlated with temperature, which was related to the “shell forming” phenomenon of slag hydration.